Oxygen diffusion in oxide crystals - tracing new routes to identify the rate limiting step of oxygen permeation through perovskite membranes - Wang, Haihui; Yang, Weishen; Tablet, Cristina; Caro, Jürgen (Diffusion Fundamentals, 2005)
Perovskites are known as mixed electric conductors because they show both electronic (via electron holes) and ionic (via oxygen vacancies) conductivity. Since the electron conductivity is orders of magnitude higher than the ionic one, oxygen vacancy bulk diffusion is regarded as the rate limiting step in oxygen permeation through perovskites. However, for thin perovskite layer the rate of this bulk diffusion process starts to compete with the so called surface reaction which represents the dissociative adand desorption of the oxygen molecule and the incorporation/release of the oxygen ions from the perovskite framework. The oxygen permeation flux through the perovskite membrane made of Ba 0.5 Sr 0.5 Co 0.8 Fe 0.2 O 3-δ (BSCF) has been measured as a function of both the temperature, membrane thickness and the oxygen pressure gradient across the membrane. A combined bulk diffusion/surface reaction model can be used to understand the mechanism of the oxygen transport. The limiting step of the oxygen transport was found to be the bulk oxygen ion diffusion coefficient (D i ) for the BSCF perovskite at temperatures above 700 ℃. Furthermore, the oxygen vacancy diffusion coefficient (D v) can be deduced from the dependence of the oxygen permeation flux on the oxygen pressure gradient provided that the oxygen vacancy δ are known. From permeation measurement on the BSCF membrane tube under study, is found to be between 2.82×10 -5 cm2/s at 900 ℃ and 0.82×10 -5 cm2/s at 700 ℃.